Empowerment of Natural Resources and the Environment as a Livelihood for Rural Communities - Muhammad, Alfian; Muhammad Amin; Safwan Kamal; Zubir; Safwandi; Zefri Maulana (SEURAYA Jurnal Pengabdian Kepada Masyarakat, 2023)
The aim of this service is to examine community empowerment efforts in optimizing the potential of natural resources and the environment as a source of livelihood, as well as exploring the role of women in the production process and management of natural resources and the environment as a livelihood for rural communities. The location of this service is in Afdeling II Bukit Village, Birem Bayeun District, East Aceh Regency. The problems that occur in Afdeling II Bukit Village are the lack of community awareness of the importance of diversifying livelihoods to reduce dependence on a single sector, the lack of innovation in the production of local products that can provide added value and contribute to the competitiveness of the local economy, and then, the lack of concern for resource conservation. nature and the environment in achieving sustainable and inclusive development in Afdeling II Bukit Village. Support from the government and various parties is highly expected to continue to encourage and develop initiatives to achieve better progress for the community and environment of Afdeling II Bukit Village.